Nutrient criteria to achieve New Zealand’s riverine macroinvertebrate targets - Adam D. Canning; Michael K. Joy; Russell G. Death (PeerJ, 2021)
Waterways worldwide are experiencing nutrient enrichment from population growth and intensive agriculture, and New Zealand is part of this global trend. Increasing fertilizer in New Zealand and intensive agriculture have driven substantial water quality declines over recent decades. A recent national directive has set environmental managers a range of riverine ecological targets, including three macroinvertebrate indicators, and requires nutrient criteria be set to support their achievement. To support these national aspirations, we use the minimization-of-mismatch analysis to derive potential nutrient criteria. Given that nutrient and macroinvertebrate monitoring often does not occur at the same sites, we compared nutrient criteria derived at sites where macroinvertebrates and nutrients are monitored concurrently with nutrient criteria derived at all macroinvertebrate monitoring sites and using modelled nutrients. To support all three macroinvertebrate targets, we suggest that suitable nutrient criteria would set median dissolved inorganic nitrogen concentrations at ~0.6 mg/L and median dissolved reactive phosphorus concentrations at ~0.02 mg/L. We recognize that deriving site-specific nutrient criteria requires the balancing of multiple values and consideration of multiple targets, and anticipate that criteria derived here will help and support these environmental goals.